2019
DOI: 10.1515/chem-2019-0097
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1,8-Naphthyridine Derivatives: Design, Synthesis and in vitro screening of their cytotoxic activity against MCF7 cell line

Abstract: A series of new 2-phenyl-7-methyl-1,8-naphthyridine derivatives with variable substituents at C3 were synthesized for an in vitro evaluation of their anticancer activity against human breast cancer cell line (MCF7). On one hand, compounds 3f, 6f, 8c, and 10b showed IC50 values (6.53, 7.88, 7.89, 7.79 μM, respectively) compared to that of the mentioned drug staurosparine (IC50 = 4.51 μM). On the other hand, derivatives 10c, 8d, 4d, 10f and 8b displayed better activity than staurosporin with IC50 values (1.47, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Gc.Mass analysis in the present study confirmed the presence of some compounds in A.falvus metabolites as alchole, phenol, steriods, terpinoids, silane and others that characterized by their antioxidant, antimicrobial and anticancer activities; this concurs with other previous studies (Verma, 2006;Mou et al, 2013;Kim et al, 2015;Govindappa et al, 2017;Tamil et al, 2017;Karakuş et al, 2018;Al-Romaizan et al, 2019;Purnamasari et al, 2019;. In addition, the presence of some compounds determined herein as Carophylla and Tricyclo-carboxylic acid that reported in the previous studies by their potent anticancer activities (Verma, 2006;Jelena & Maja, 2015;Al-Romaizan et al, 2019). In this regarding, presence of ether and pyrazole compounds in A. flavus extract play major roles as antioxidant and antimicrobial activities; this concurs with that reported in the previous studies (Jelena & Maja, 2015;Srivastava et al, 2015;Narra et al, 2017;Yadav et al, 2018).…”
Section: Candida Albicanssupporting
confidence: 93%
“…Gc.Mass analysis in the present study confirmed the presence of some compounds in A.falvus metabolites as alchole, phenol, steriods, terpinoids, silane and others that characterized by their antioxidant, antimicrobial and anticancer activities; this concurs with other previous studies (Verma, 2006;Mou et al, 2013;Kim et al, 2015;Govindappa et al, 2017;Tamil et al, 2017;Karakuş et al, 2018;Al-Romaizan et al, 2019;Purnamasari et al, 2019;. In addition, the presence of some compounds determined herein as Carophylla and Tricyclo-carboxylic acid that reported in the previous studies by their potent anticancer activities (Verma, 2006;Jelena & Maja, 2015;Al-Romaizan et al, 2019). In this regarding, presence of ether and pyrazole compounds in A. flavus extract play major roles as antioxidant and antimicrobial activities; this concurs with that reported in the previous studies (Jelena & Maja, 2015;Srivastava et al, 2015;Narra et al, 2017;Yadav et al, 2018).…”
Section: Candida Albicanssupporting
confidence: 93%
“…According to literature survey the compounds bearing 1,8-Naphthyridine scaffold can produce their anticancer potency via different molecular mechanisms such as; protein kinase inhibition like topoisomerase II, c-Met, VEGFR-2, EGFRPDGFR-β, apoptosis inducing effect and via enhancing the activity of different proapoptotic proteins such as caspases, p53, Bax/BCl-2 [32,33]. In addition, various 1,8-naphthyridine derivatives intercalate the adjacent base pairs of DNA resulting in inhibition of DNA duplication or transcription and suppression the growth of cancer cells [34].…”
Section: Biological Evaluationmentioning
confidence: 99%
“…e naphthyridine framework exists in a number of natural and synthetic substances with various chemical reactivities and exceptional physicochemical [1] and biological properties [2,3], which include anticancer, [4] HIV-I inhibitor, [5] anticonvulsant, [6] antimalarial [7], and anti-Alzheimer [8]. Among the six possible (1,5−, 1,6−, 1,7−, 1,8−, 2,6−, and 2,7−) isomeric pyridopyridines, [9,10] 1,8-naphthyridines and their derivatives have diverse potential in clinical and medicinal chemistry due to their anti-inflammatory, [11] antimalarial, [12] antihypertensive, [13] gastric antisecretory, [14] antiplatelet aggregation, [15] AChE inhibitory, [16] antihistaminic, [2] antimicrobial [17,18], and anticancer [19][20][21] activities (Figure 1). Additionally, they have potential in physical chemistry as fluorescent sensors [22].…”
Section: Introductionmentioning
confidence: 99%
“…Vosaroxin (formerly voreloxin) is a first-in-class anticancer agent that intercalates DNA and inhibits topoisomerase II, inducing site-selective double-strand breaks (DSB), G2 arrest, and apoptosis [23,24]. Chemical modifications of the naphthyridine ring, including conversion into other similar ring systems, have been known to increase the anticancer activity of these compounds [21,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation